Model of Quality of Life Development for Patients with Cerebrovascular Diseases of Banthi subdistrict, Banthi district, Lumphun province - konthiang, kattiyaporn; Songprakun, Wallapa; Keowsingh, Petcharin (Journal of Nursing, Siam University, 2021)
This study aims to examine a model of quality of life development for patients with cerebrovascular diseases of Banthi Subdistrict, Banthi District, Lumphun Province. The samples are thirteen stroke-patients and thirteen principal-caregivers, including fifteen key informants. Data was collected using Stroke Impact Scale: SIS) Thai version questionnaire (Khampolsiri, Pothiban, Sucamvang, & Panuthai, 2006), in-depth interviews, and group discussion related to ECCM components. Wilcoxon Signed-Rank test and descriptive data were used to analyze data. Finding illustrated that the model of quality of life development for patients with cerebrovascular diseases of Banthi Subdistrict, Banthi District, Lumphun Province was consistent with the community’s context. Steakholders in the community concern about the significances of quality of life development continuously and efficiency. The result showed significant difference between mean score at pretest and posttest of hand function (p< 0.05). However, there were no differences between mean scores at pretest and posttest of other components, strength, communication, memory, emotion, social participation, activity of daily living, and mobility. In conclusion, stakeholders in the community Banthi Subdistrict, Banthi District, Lumphun Province were satisfied with the model of quality of life development for patients with cerebrovascular diseases, cooperated with continuous improvement of quality of life. Health care team had a model for implementing continuously and systematically, consistency with community context. Moreover, a guideline for quality of life development for patients with cerebrovascular diseases from this study can be applied for further study in special care of specific aspect, especially, for patients in rehabilitation phase.